Księga jako element mitologii świata przedstawionego w polskiej powieści fantastycznej - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
Polish science fiction creates the presented world as dominated by totalitarian system. The government controls the distribution of information. Oposing that, citizens create their own means of diffusing information, designated as the Book. The Book makes readers realize the contradiction between the rules imposed by government and their own conscience. Besides, the act of reading symbolizes the process of growing to reach the truth. The very motif of the Book may be understood as allusion to unofficial literature, that emerged in the early 80. years, while Polish science fiction was caming into being.